Structure of the complexes formed between sodium dodecyl sulfate and a charged and uncharged ethoxylated polyethyleneimine: Small-angle neutron scattering, electromotive force, and isothermal titration calorimetry measurements - Li, Y; Xu, R; Couderc, S; Bloor, D; Warr, J; Penfold, J; Holzwarth, J; Wyn-Jones, E (2001)
A poly(ethylene oxide) derivative of polyethyleneimine behaves like a strong polyelectrolyte at pH = 2.5 and a neutral polymer at pH 10. Both the charged and uncharged versions of this polymer bind strongly to the surfactant sodium dodecyl sulfate (SDS) with no phase separation taking place. Binding isotherms were measured using a dodecyl sulfate electrode, and these data were complemented with isothermal titration calorimetry (ITC) measurements. Small-angle neutron scattering measurements were also carried out at some specific concentrations in the binding region at phs 2.5, 5.5, and 10. With the exception of one measurement, bound micelles were detected and their aggregation numbers could be evaluated. For the SDS/polymer system at pH 10, the polymer/surfactant complex contains 6-8 bound SDS micelles per polymer molecule at the binding limit. In a solution of 6.5 mM SDS/0.5% w/v polymer at pH 10, bound SDS exists in a nonaggregated form. A detailed examination of the ITC data for the SDS/0.5% w/v polymer system shows at pH 10 that this spot solution occurs in a narrow SDS concentration range immediately following the onset of binding and proceeding until the formation of proper bound micellar aggregates was detectable, whose presence and growth were characterized in the ITC experiments by a steplike decrease in the enthalpy per injection as a function of increasing SDS concentration. These data suggest that the absence of proper micellar aggregates is an inherent consequence of the binding mechanism in the early stages of SDS binding to ethoxylated polyethyleneimines.